Dr. Empirical Model For Measuring The Impact of Corporate Social Responsibility on Financial Performance of South African Mining Companies - Emmanuel Obinali OBIOHA; Solomon Olanrewaju AKINBOYE (International Journal of Environmental, Sustainability, and Social Science, 2024)
Since 1950, corporate social responsibility has been receiving scholarly and managerial importance yet its implementation and evaluation remains untapped. The non-existence of a robust tool for measuring the impact of corporate social responsibility on financial performance of South African mining companies via social and environmental dimensions has continued to be a serious concern in literature and in practice. Thus, the focus is to develop this model by collecting a quantitative data through a census of 45 mining companies listed at Johannesburg Stock Exchange (JSE), located in Gauteng and subscribing to Socially Responsible Investment (SRI) index and empirically testing the established theoretical linkages of corporate social responsibility (i.e. social and environmental performance) across their factors/elements with measures of financial performance and putting the tested linkages together. Factor analysis was utilized for data reduction, Chi-square tested for association between categorical variables, Cronbach alpha for internal consistency and reliability of instruments. The findings revealed significant associations between corporate social responsibility, corporate social and environmental performance. Similarly, results suggest that corporate social responsibility performance can translate to financial performance through the elements of social and environmental performance. The implication is that corporate managers can achieve competitive advantage and increase profit by factoring the elements of social and environmental performance, shareholder value, revenue, operational efficiency and access to capital into their decision making models/systems.